Diabetes Mellitus And The Therapeutic Potential Of Phaleria Macrocarpa Extract: A Review - Azis Mangara; Shanty Maria Lisanora Fernanda; Norong Peranginangin; Riska Wani Eka Putri; Defri Elias Simatupang; Noradina Noradina; Meriani Herlina (The International Science of Health Journal, 2024)
Background: The rising prevalence of diabetes mellitus globally necessitates the exploration of alternative treatment options. Phaleria macrocarpa, known for its traditional use in the treatment of various ailments, has garnered interest as a potential adjunctive therapy for diabetes. Objective: This review synthesizes current research on the efficacy and safety of Phaleria macrocarpa in the management of diabetes, outlining its therapeutic potential, pharmacological mechanisms, and future research directions. Methods: A comprehensive literature search was conducted, encompassing studies that investigated the effects of Phaleria macrocarpa on diabetes-related parameters in preclinical and clinical settings. Results: The collected data suggest that Phaleria macrocarpa may improve blood glucose control and insulin sensitivity. Several studies indicate a positive effect on metabolic parameters in diabetes. However, the safety profile warrants further investigation, as does the standardization of dosages. Conclusions: While preliminary findings show promise for the integration of Phaleria macrocarpa into diabetes care, extensive clinical trials are required to confirm efficacy and establish safety. Moreover, a better understanding of the plant's bioactive compounds, their mechanisms of action, and potential interactions with standard diabetes treatments is essential. The cultural importance of Phaleria macrocarpa supports its continued investigation, recognizing the need to respect and integrate traditional knowledge with contemporary medical practices.